Project-Based Learning and Its Contribution to Student Character Development in Secondary Education - Rospa; Dodi Irawan (LPPM Sekolah Tinggi Teknologi Nusantara Lampung, 2025)
Project-based learning has increasingly been recognized as an effective pedagogical approach for fostering student character development in secondary education. This study examines the implementation of project-based learning as a strategy to strengthen student character development within a secondary school context, particularly through structured school management practices. Employing a qualitative descriptive design, data were collected through interviews, observations, document analysis, and questionnaires involving school leaders, teachers, and students. The data were analyzed thematically to identify patterns related to planning, implementation, supervision, and learning outcomes. The findings reveal that project-based learning contributes positively to student character development, especially in dimensions related to collaboration, creativity, independence, and social responsibility. Effective implementation is supported by systematic school management, including structured scheduling, clear role distribution, and alignment between project themes and learning objectives. However, the study also identifies several challenges, such as limited teacher involvement in the planning phase, uneven student engagement, insufficient operational guidelines, and constraints in funding and external supervision. These factors affect the consistency and depth of character development outcomes, particularly in higher-order skills such as critical reasoning. The study contributes to the literature on educational innovation by highlighting the importance of integrative management practices in maximizing the potential of project-based learning for character education. The findings suggest that inclusive planning, clear standard operating procedures, stakeholder involvement, and continuous evaluation are essential to enhance the effectiveness and sustainability of project-based learning initiatives. These insights offer practical implications for school leaders, educators, and policymakers seeking to promote holistic student development through innovative instructional approaches in diverse educational settings.